Pengaruh Pelatihan dan Pengalaman Kerja Terhadap Kinerja Guru di Sekolah Lentera Harapan Toraja - Irnawaty Irnawaty; Mince Batara; Helba Rundupadang (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to determine the effect of training and work experience on teacher performance at the Lentera Harapan Toraja School. This research data was collected by distributing questionnaires to 60 teachers. This research uses quantitative research. Data were analyzed using the SPSS 16 program. Based on the results of this research, it shows that partially training has an influence but is not significant on teacher performance and work experience has a significant influence on teacher performance. And simultaneously training and work experience together have a significant influence on performance